“Do Good, Have Good”: A Serial Mediation Analysis of CSR with Customers’ Outcomes - Ahmed, Ishfaq; Nazir, Mian Sajid; Ali, Imran; Khalid, Arooj; Shaukat, Muhammad Zeeshan; Anwar, Farooq (Frontiers in Psychology, 2020)
Corporate social responsibility (CSR) is envisaged to offer several outcomes and while customer-specific consequences are unclear or have not obtained due attention, there is a dearth of literature that focuses on perceptual, attitudinal and behavioral outcomes in tandem. Against this backdrop, this study entails the investigation of perceptual (service quality), attitudinal (affective commitment) and behavioral (customer citizenship behavior) outcomes of CSR through a serial mediation mechanism. A total of 994 responses obtained from fast-food restaurants, highlight the fact that CSR influences service quality, affective commitment, and customer citizenship behavior. Moreover, it is witnessed that CSR influences customer citizenship behavior indirectly as well, as the serial mediation mechanism is also proved. The practical and theoretical usefulness of the study is also provided at the end.